Future directions of the National Institutes of Health Science of Behavior Change Program - Keller, Chandra (Transl Behav Med, 2021)
BACKGROUND: The National Institutes of Health Science of Behavior Change Common Fund Program has accelerated the investigation of mechanisms of behavior change applicable to multiple health behaviors and outcomes and facilitated the use of the experimental medicine approach to behavior change research. PURPOSE: This commentary provides a brief background of the program, plans for its next phase, and thoughts about how the experimental medicine approach to behavior change research can inform future directions in two areas of science—reproductive health and COVID-19 vaccine uptake. CONCLUSIONS: The incorporation of a mechanisms-based approach into behavior intervention research offers new opportunities for improving health.